Continuous Consecutive Reactions with Inter‐Reaction Solvent Exchange by Membrane Separation. (27th September 2016) - Peeva, Ludmila; Da Silva Burgal, Joao; Heckenast, Zsofia; Brazy, Florine; Cazenave, Florian; Livingston, Andrew
Abstract: Pharmaceutical production typically involves multiple reaction steps with separations between successive reactions. Two processes which complicate the transition from batch to continuous operation in multistep synthesis are solvent exchange (especially high‐boiling‐ to low‐boiling‐point solvent), and catalyst separation. Demonstrated here is membrane separation as an enabling platform for undertaking these processes during continuous operation. Two consecutive reactions are performed in different solvents, with catalyst separation and inter‐reaction solvent exchange achieved by continuous flow membrane units. A Heck coupling reaction is performed in N, N ‐dimethylformamide (DMF) in a continuous membrane reactor which retains the catalyst. The Heck reaction product undergoes solvent exchange in a counter‐current membrane system where DMF is continuously replaced by ethanol. After exchange the product dissolved in ethanol passes through a column packed with an iron catalyst, and undergoes reduction (>99 % yield).